Antonello da Messina: l’ opera completa - Hutchings, Patrick (Sophia, 2009)
Antonello da Messina’s Annunciation with the Blessèd Virgin sola breaks with iconic convention, so inviting new interpretations of the theme. The Rome exhibition of 2006 allowed one to compare Antonello with van Eyck: Antonello seemed pre-modern. This review discusses three important essays on the Annunciation (see the last three keywords). All three perceptive essays raise theological and phenomenological issues directly related to the almost unique iconic representation which Antonello gives us.